If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 9x + 1 + -3x Reorder the terms: 13 = 1 + 9x + -3x Combine like terms: 9x + -3x = 6x 13 = 1 + 6x Solving 13 = 1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 13 + -6x = 1 + 6x + -6x Combine like terms: 6x + -6x = 0 13 + -6x = 1 + 0 13 + -6x = 1 Add '-13' to each side of the equation. 13 + -13 + -6x = 1 + -13 Combine like terms: 13 + -13 = 0 0 + -6x = 1 + -13 -6x = 1 + -13 Combine like terms: 1 + -13 = -12 -6x = -12 Divide each side by '-6'. x = 2 Simplifying x = 2
| 8x+10x=-2(x-2)+3 | | 5m+5=2(m+2)+m+1 | | graphx+2y=10 | | (3x+6)+(x-10)+(x-11)=180 | | .02f+0.6(f+20)=-8+0.4f | | Y+6=-4(x-4) | | 6n-60=0 | | 24=-4(3w+3) | | 2y=-4x-6 | | 6[x-1]=9[x-4] | | -10n+12=-3n-9 | | 3c+15-2=2c+12+2 | | 4y-3x=24 | | n-15.43=-9.2 | | 4b+24=2b+10+2 | | 35=7v-6 | | 2X+18=2x-3 | | (2x)=(y-x) | | 9x+15=15x | | 8x+4-8=4x+12 | | R=2m+2s | | x+69=0 | | 2y=(4x^2)-6 | | 2x-2-x=4+4x+6 | | (-9)2(-1)5= | | 3x^2+22x+4=-20 | | x+14=(-6) | | (2y-5)+(9y-8)= | | 2(3)+2w=46 | | 5y+5+2=4y+8-6 | | 6sin^2(3x)=3 | | 3.14r*2=314 |